2007
DOI: 10.1104/pp.106.094102
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lipid Rafts from Medicago truncatula Root Plasma Membranes: A Proteomic Study Reveals the Presence of a Raft-Associated Redox System

Abstract: Several studies have provided new insights into the role of sphingolipid/sterol-rich domains so-called lipid rafts of the plasma membrane (PM) from mammalian cells, and more recently from leaves, cell cultures, and seedlings of higher plants. Here we show that lipid raft domains, defined as Triton X-100-insoluble membranes, can also be prepared from Medicago truncatula root PMs. These domains have been extensively characterized by ultrastructural studies as well as by analysis of their content in lipids and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
209
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(233 citation statements)
references
References 79 publications
22
209
0
2
Order By: Relevance
“…Association of the cytochrome here identified as AIR12 to the PM was previously demonstrated by analytical Suc gradient centrifugation of plant microsomes (Preger et al, 2005). This result is supplemented by recent proteomic studies that identified AIR12 as a PM protein (Dunkley et al, 2006) bound to the external face of the PM by means of a GPI anchor (Borner et al, 2003) and in association with lipid rafts (Lefebvre et al, 2007). AIR12 has been reported among secreted proteins of Medicago truncatula cell cultures, suggesting that the GPI anchor is cleaved under particular conditions with release of the protein (Kusumawati et al, 2008).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Association of the cytochrome here identified as AIR12 to the PM was previously demonstrated by analytical Suc gradient centrifugation of plant microsomes (Preger et al, 2005). This result is supplemented by recent proteomic studies that identified AIR12 as a PM protein (Dunkley et al, 2006) bound to the external face of the PM by means of a GPI anchor (Borner et al, 2003) and in association with lipid rafts (Lefebvre et al, 2007). AIR12 has been reported among secreted proteins of Medicago truncatula cell cultures, suggesting that the GPI anchor is cleaved under particular conditions with release of the protein (Kusumawati et al, 2008).…”
Section: Discussionsupporting
confidence: 56%
“…A DOMON-plus-cytochrome b561 protein (AC147406_ 8.1) has recently been detected in lipid rafts of M. truncatula roots together with AIR12 and other redox proteins (Lefebvre et al, 2007;i.e. orthologs of SKU5 and FQR1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…html). Protein association with detergent-resistant membranes (DRM) was inferred from the DRM proteomes of M. truncatula roots either non-mycorrhizal (Lefebvre et al 2007;Guillier et al 2014) or mycorrhizal (Lemaître-Guillier, personal communication). Functional classification was performed according to the FunCat scheme (Ruepp et al 2004).…”
Section: Digital Immunoblotting and Protein Characterizationmentioning
confidence: 99%
“…The mechanisms by which the AM-responsive proteins may associate with the PM fraction were further analyzed using in silico prediction programs for alpha-helical TM regions, lipid modifications, and N-terminal signal sequence on the dataset listed in Table 1. Because proteins also can be recruited to lateral lipid patches that form detergent-resistant microdomains (DRM) within the membrane (Lefebvre et al 2007;Guillier et al 2014), we also searched the DRM proteomes of M. truncatula roots for the presence of AMresponsive proteins. Figure 4b shows that alpha-helix and palmitoylation were the prevalent candidate processes, as predicted for 78 and 58% of the 82 proteins, respectively.…”
Section: Analysis Of the Am-responsive Proteinsmentioning
confidence: 99%